The Meaning and Limitations of a Notary's Obligation in Safeguarding the Interests of the Parties in Legal Acts from the Perspective of Legal Certainty - Rachman, Isnilah Nur; Widhiyanti, Hanif Nur; Wisnuwardhani, Diah Aju (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This research aims to the meaning and limitations of a notary's obligation to “safeguard the interests of the parties involved in legal acts” as stipulated in Article 16 paragraph (1) letter a of the Indonesian Notary Position Act. This provision raises ambiguity or lack of clarity due to the insufficient explanation in the law, particularly regarding the phrase "safeguard the interests of the parties." Using a normative juridical research method with a legislative and conceptual approach, with legal materials consisting of primary and secondary legal sources to be analyzed through grammatical interpretation, this study explores the extent to which notaries are required to act neutrally, faithfully, and independently in carrying out their duties. The research finds that the ambiguity of the provision may lead to varying interpretations among notaries, which in turn affects the consistency of the law's application in practice. There is a need for more detailed or explicit guidance in the law to avoid multiple interpretations that could trigger ambiguity in the performance of a notary's duties. This study emphasizes the importance of reformulating the legal provisions to ensure that the notary's obligations in safeguarding the interests of the parties involved are clearer, thereby ensuring legal certainty and protection for all parties involved in legal acts.